Effect of Impact Load on Concrete Containing Recycled Tire Rubber Aggregate With and Without Fire Exposure - Muhammad, Muhammad Arf; Abdullah faraj, Wrya Abdulfaraj; Abdul-Kadir, Mohamed Raouf (Kurdistan Journal of Applied Research, 2020)
Over one billion tires are disposed into the environment each year and this has become a major environmental issue in the globe. Recycling of these waste tire rubbers in concrete has gained attention from researchers all around the world. In this study, the impact resistance of rubberized concrete exposed to fire is investigated experimentally in the laboratory. For that purpose, sixty specimens were made with five different mixes replacing their sand content partially with different percentages of tire rubber by weight ratios of 0% control, 6%, 12%, 18% and 24%. The water/cement ratio was kept constant at 0.393 in all the mixes. In each mix, fifteen concrete specimens with the size of (150 x 150 x 73) mm were prepared to expose to fire. Every three specimens were gradually exposed to fire for four various durations of (0, 15, 30, and 45) minutes. Each specimen was then tested in a drop-weight impact machine by dropping 2240-gr and 4500-gr hammers from heights of 280 mm and 450 mm. The average impact energy of three identical specimens required for the occurrence of the final fracture was calculated. The investigational results are compared with results of control samples. It is found that the impact energy considerably increased with an increase of the rubber replacement. It is, also, noted that any increase in the burning period of specimens results in a reduction of the impact energy and more early crushing of the rubberized concrete.